1990
DOI: 10.1007/bf00119007
|View full text |Cite
|
Sign up to set email alerts
|

Growth and water potential of j-rooted loblolly and eastern white pine seedlings over three growing seasons

Abstract: Application. Root deformations, such as j-rooting, have long been considered detrimental to forest seedling growth. Based on the results of this study, j-rooting will not result in water stress or lead to reductions in growth three years after planting. Tree planters need to be concerned with planting seedlings quickly and at the correct depth. Instructing planters to avoid j-roots by pulling back up on the seedlings when they are placed in the bottom of planting hole may do more damage than good since the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…In New Jersey, a researcher reported no harmful effects of planting L-or J-roots in "poor slits" on survival or early growth of shortleaf pine seedlings [64]. This is in agreement with most trials where bent roots of other pine species have been planted in deep holes [63,65,66]. Little [64] excavated shortleaf pines that were planted with an L-, J-, or U-root and concluded that although some roots were twisted and others had few roots on one side, "all the excavated seedlings had developed spreading root systems indicating that root systems had largely recovered from planting damage.…”
Section: Bent Rootssupporting
confidence: 74%
“…In New Jersey, a researcher reported no harmful effects of planting L-or J-roots in "poor slits" on survival or early growth of shortleaf pine seedlings [64]. This is in agreement with most trials where bent roots of other pine species have been planted in deep holes [63,65,66]. Little [64] excavated shortleaf pines that were planted with an L-, J-, or U-root and concluded that although some roots were twisted and others had few roots on one side, "all the excavated seedlings had developed spreading root systems indicating that root systems had largely recovered from planting damage.…”
Section: Bent Rootssupporting
confidence: 74%
“…Harrington and How-ell (1998) found that growth of Pinus taeda was significantly greater when trees were planted with straight roots rather than deformed or pruned taproots. In contrast, Seiler et al (1990) found that Pinus taeda and Pinus strobus with J-roots did not show reduced growth or increased water stress after three years when they were planted with the root collar at grade. After five years, Carvell and Kulow (1964) found an upper layer of superficial roots had formed on Pinus strobus trees planted 15.2 cm below grade and original roots were growing up toward the soil surface.…”
mentioning
confidence: 79%
“…One of the reasons for unfavorable growth of some deeply planted SP trees is a tendency for roots to circle, bend, or otherwise become deformed (Seiler et al 1990). Harrington and How-ell (1998) found that growth of Pinus taeda was significantly greater when trees were planted with straight roots rather than deformed or pruned taproots.…”
mentioning
confidence: 99%
“…The quadratic relation between planting depth and dry matter weight indicating a rise and fall of dry matter weight with a plateau is in conformity with other authors. Seiler et al (1990) and South (1991) reported increased seedling mortality for shallow planting, while VanderSchaaf and South (2003) reported smaller diameter preparation and planting. Finally, the study showed the root and rootlet preparation methods and the depth of planting of teak stumps required to achieve maximum biomass production to ensure its high survival rate and if adopted by tree growers can reduce planted teak stump mortality considerably.…”
Section: Discussionmentioning
confidence: 99%